Six cases of mass murder - Columbine, Virginia Tech, Aurora Movie Theatre, Sandy Hook, Pulse Nightclub, Las Vegas: explaining why people kill - Weatherby, Georgie Ann (The Edwin Mellen Press, 2018)
Introduction/theoretical preview -- Active shooters: unraveling the mysteries -- Columbine killers Eric Harris and Dylan Klebold -- Virginia Tech killer Seung-Hui Cho -- Aurora Movie Theatre killer James Holmes -- Sandy Hook Elementary School killer Adam Lanza -- Pulse Nightclub killer Omar Mateen -- Las Vegas concert killer Stephen Paddock -- Conclusion: what have we learned?